Composite adhesive tape, display module and OLED screen
Patent Information
- Application Number
- CN202522570211.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Utility models(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-03
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2035-12-03
AI Technical Summary
[0003]然而,当前市场上广泛使用的传统遮光胶带,在实际应用过程中逐渐暴露出诸多关键技术缺陷,主要包括以下几点:(1)酸性腐蚀风险:传统胶带多采用普通丙烯酸酯胶粘剂,长期处于3C产品内部高温、密闭环境中,易析出酸性物质,腐蚀PCB电路板、屏幕排线等精密元件,导致产品出现显示故障、接触不良等问题,缩短3C产品使用寿命
[0038]本实用新型提供的复合胶带可避免酸性物质析出对电子产品内部精密元件的腐蚀,相比传统胶带产品,可延长电子产品使用寿命;遮光效果稳定,透光率≤0.05%,可完全隔绝电子产品内部LED背光、摄像头补光灯等光线干扰,在手机屏幕组装中,可避免光线渗漏导致的显示偏色;在摄像头模组中,可防止杂光影响成像清晰度,提升产品性能;轻薄柔性结构可精准适配狭小空间与曲面装配需求,降低组装损耗;耐高温高湿,可耐受电子产品生产焊接高温及极端环境使用,贴合后无起翘、脱胶现象。
Smart Images

Figure CN224883971U_ABST
Abstract
Description
Technical Field
[0001] This utility model belongs to the field of tape technology, specifically relating to a composite tape, a display module, and an OLED screen. Background Technology
[0002] With the rapid development of consumer electronics (3C) products, such as smartphones, tablets, and laptops, towards ultra-thinness, high integration, and high performance, their internal components are arranged extremely closely. As a key functional material, light-shielding tape plays an irreplaceable role within 3C products. It is primarily used to prevent light leakage and reflection in the gaps between the screen, camera module, sensor, PCB board, and casing, thereby ensuring the accuracy of displayed colors, the purity of camera images, and the signal stability of optical sensors.
[0003] However, the traditional light-blocking tapes widely used in the market have gradually revealed many key technical defects in actual applications, mainly including the following: (1) Risk of acid corrosion: Traditional tapes mostly use ordinary acrylic adhesives. When in the high-temperature and closed environment inside 3C products for a long time, acidic substances are easily released, which corrode precision components such as PCB circuit boards and screen cables, leading to display failures, poor contact and other problems, and shortening the service life of 3C products. (2) Insufficient light-blocking performance: Some low-cost light-blocking tapes only achieve light blocking through a single black substrate. In the application of high-brightness screens or camera modules of 3C products, light leakage is likely to occur, interfering with the accuracy of display colors or the imaging quality of cameras. In addition, some tapes are prone to peeling after bonding due to changes in ambient temperature, further reducing the light-blocking effect. (3) Poor environmental tolerance: The temperature resistance and moisture resistance of existing tapes generally cannot match the environmental requirements of 3C products from production assembly (high-temperature welding) to daily use (-20℃~60℃), and the adaptability is poor.
[0004] CN213388482U discloses a light-shielding tape used to cover the end face of a display panel. This light-shielding tape further includes an insulating substrate layer, a composite metal layer on the upper surface of the insulating substrate layer, and a single metal layer on the lower surface of the insulating substrate layer. The surface of the composite metal layer opposite to the insulating substrate layer is covered with an ink layer, and the surface of the single metal layer opposite to the insulating substrate layer is covered with a black conductive adhesive layer. The single metal layer is an aluminum layer or a copper layer. This achieves good electromagnetic shielding effect and greatly reduces the warping phenomenon of the metal layer in the tape on the liquid crystal screen, but its high-temperature stability is poor.
[0005] CN205188195U discloses a light-blocking tape comprising two layers of transparent release film and a black PET film. One layer of transparent release film is bonded to one side of the black PET film using acrylic adhesive. The other side of the black PET film is coated with a white printed coating and bonded to the other transparent release film using acrylic adhesive. This tape exhibits good high-temperature resistance and good light reflection, providing excellent light-blocking performance; however, prolonged use may result in the release of acidic substances.
[0006] Therefore, developing an acid-free composite tape with good light-blocking effect and excellent high temperature and humidity resistance is a technical problem that urgently needs to be solved in this field. Utility Model Content
[0007] To address the shortcomings of existing technologies, the purpose of this utility model is to provide a composite tape, a display module, and an OLED screen. The composite tape does not release acidic substances during long-term use, has excellent light-blocking effect, good adhesion, and resistance to high temperature and humidity. At the same time, the composite tape is thin, making it suitable for assembly in the confined spaces inside electronic products.
[0008] To achieve this objective, the present invention adopts the following technical solution:
[0009] In a first aspect, this utility model provides a composite tape, the composite tape comprising a composite substrate layer, an adhesive layer and a release liner layer arranged sequentially;
[0010] The composite substrate layer includes a base film layer, a black ink layer, and an anti-fingerprint coating;
[0011] The adhesive layer includes an acid-free pressure-sensitive adhesive layer.
[0012] The composite tape provided by this utility model includes a composite substrate layer, an adhesive layer and a release liner layer arranged in sequence. It adopts an acid-free system and combines a high-efficiency composite light-shielding structure to give it a good light-shielding effect, achieve precise light shielding and avoid stray light interference with display and imaging effects, eliminate the corrosion of precision electronic components by acidic substances, and has good adhesion and high temperature and humidity resistance, matching the usage needs from production assembly to daily environment.
[0013] As a preferred embodiment of this invention, the base film layer comprises a polyester film layer or a polyimide layer.
[0014] As a preferred technical solution of this utility model, the thickness of the base film layer is 2-20μm, such as 2μm, 4μm, 6μm, 8μm, 10μm, 12μm, 14μm, 16μm, 18μm or 20μm, etc.
[0015] As a preferred embodiment of this invention, the black ink layer includes a carbon black ink layer.
[0016] As a preferred embodiment of this invention, the thickness of the black ink layer is 2-5 μm, such as 2 μm, 3 μm, 4 μm or 5 μm.
[0017] As a preferred embodiment of this invention, the anti-fingerprint coating comprises a water-soluble polyurethane layer.
[0018] As a preferred technical solution of this utility model, the thickness of the anti-fingerprint coating is 1-3μm, such as 1μm, 2μm or 3μm.
[0019] As a preferred embodiment of this invention, the raw materials for preparing the adhesive layer include the following components by weight:
[0020] 99-100 parts of acid-free acrylic copolymer
[0021] Hardener 0.01-1 part
[0022] Solvent 100-200 parts.
[0023] As a preferred embodiment of this utility model, the acid-free acrylic copolymer includes any one or a combination of at least two of polyacrylic resin, polyurethane-modified acrylic resin, epoxy-modified acrylic resin, silicone-modified acrylic resin, or polyester-modified acrylic resin.
[0024] As a preferred technical solution of this utility model, the curing agent includes any one or a combination of at least two of the following: diisocyanate, polyisocyanate, modified diisocyanate, modified polyisocyanate, epoxy compound, modified epoxy compound, pyridine and its derivatives, imidazole and its derivatives, metal salt chelates, hydrogen-containing double-ended or hydrogen-containing silicone oil.
[0025] As a preferred embodiment of this invention, the solvent includes any one or a combination of at least two of the following: acetone, butanone, cyclohexanone, isophorone, ethyl acetate, butyl acetate, toluene, xylene, propylene glycol monomethyl ether, or dipropylene glycol methyl ether.
[0026] As a preferred technical solution of this utility model, the thickness of the composite substrate layer is 5-28μm, such as 5μm, 7μm, 9μm, 11μm, 13μm, 15μm, 17μm, 19μm, 21μm, 23μm, 25μm, 27μm or 28μm, etc.
[0027] As a preferred embodiment of this invention, the adhesive layer includes an acid-free pressure-sensitive adhesive layer.
[0028] As a preferred embodiment of this utility model, the thickness of the adhesive layer is 10-22μm, such as 10μm, 11μm, 13μm, 15μm, 17μm, 19μm, 21μm or 22μm.
[0029] As a preferred embodiment of this utility model, the release liner layer includes a polyester release liner.
[0030] As a preferred technical solution of this utility model, the thickness of the release liner is 25-50μm, such as 25μm, 27μm, 29μm, 31μm, 33μm, 35μm, 37μm, 39μm, 41μm, 43μm, 45μm, 47μm, 49μm or 50μm.
[0031] As a preferred technical solution of this utility model, the thickness of the composite tape is 40-100μm, such as 40μm, 45μm, 50μm, 55μm, 60μm, 65μm, 70μm, 75μm, 80μm, 85μm, 90μm, 95μm or 100μm.
[0032] As a preferred embodiment of this utility model, the method for preparing the composite tape includes the following steps:
[0033] (1) A black ink layer and an anti-fingerprint coating are sequentially coated on the surface of the base film layer and dried to obtain the composite substrate layer;
[0034] (2) Apply the adhesive layer solution to the surface of the profile layer, dry it, bond it with the base film layer in the composite substrate layer, and roll it up to obtain the composite tape.
[0035] Secondly, this utility model provides a display module, which includes the composite tape described in the first aspect.
[0036] Thirdly, this utility model provides an OLED screen, which includes the display module as described in the second aspect.
[0037] Compared with the prior art, the present invention has the following beneficial effects:
[0038] The composite tape provided by this utility model can prevent the corrosion of precision components inside electronic products by acidic substances. Compared with traditional tape products, it can extend the service life of electronic products. It has a stable light-blocking effect with a light transmittance of ≤0.05%, which can completely isolate light interference from LED backlights, camera fill lights and other internal light sources in electronic products. In mobile phone screen assembly, it can prevent color distortion caused by light leakage. In camera modules, it can prevent stray light from affecting image clarity and improve product performance. Its thin and flexible structure can be precisely adapted to the assembly needs of narrow spaces and curved surfaces, reducing assembly losses. It is resistant to high temperature and humidity and can withstand the high temperature of electronic product manufacturing and welding and extreme environments. After bonding, there is no peeling or delamination. Attached Figure Description
[0039] Figure 1 A cross-sectional structural diagram of the composite tape provided by this utility model;
[0040] Among them, 1-release material layer, 2-adhesive layer, 3-base film layer, 4-black ink layer, 5-anti-fingerprint coating, 6-composite substrate layer. Detailed Implementation
[0041] The technical solution of this utility model will be further described below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely illustrative of this utility model and should not be considered as specific limitations thereof.
[0042] The information sources for some of the raw materials used in the specific embodiments of this utility model are as follows:
[0043] Acid-free acrylic copolymer: DIC, model CT-6030;
[0044] PET: Toray, Lumirror series;
[0045] Polyimide: Guofeng New Materials, GL series;
[0046] Carbon black ink: 10 items, grade 9000 series;
[0047] Water-soluble polyurethane: Sansheng Chemical, brand name PU-3109.
[0048] Preparation Example 1
[0049] This preparation example provides an acid-free pressure-sensitive adhesive, the raw materials for which the acid-free pressure-sensitive adhesive is prepared include the following components:
[0050] 100 parts of acid-free acrylic copolymer
[0051] 0.5 parts hexamethylene diisocyanate
[0052] 150 parts acetone;
[0053] The preparation method of the acid-free pressure-sensitive adhesive includes the following steps:
[0054] (1) According to the above formula, weigh acrylic acid and 145 parts of acetone into the mixing tank, stir for 10 min, then add a mixed solution of hexamethylene diisocyanate and 5 parts of acetone and stir for 30 min to obtain the acid-free pressure-sensitive adhesive.
[0055] Preparation Example 2
[0056] The only difference from Preparation Example 1 is that the acid-free acrylic copolymer was replaced with an equal amount of acrylate polymer (purchased from Anzo Chemical, Y-1300), while the amounts of other components and the preparation method were the same as in Example 1.
[0057] Example 1
[0058] This embodiment provides a composite tape with a total thickness of 70μm, and the cross-sectional structure is shown in the figure below. Figure 1 As shown, it includes a release liner layer 1, an adhesive layer 2, a base film layer 3, a black ink layer 4, an anti-fingerprint coating 5, and a composite substrate layer 6 arranged sequentially.
[0059] Among them, the profile layer 1 is a PET layer with a thickness of 50μm;
[0060] Adhesive layer 2 uses the acid-free pressure-sensitive adhesive from Preparation Example 1, with a thickness of 13 μm;
[0061] The base film layer 3 is a polyimide layer with a thickness of 3 μm;
[0062] Black ink layer 4 is a carbon black ink layer with a thickness of 2μm;
[0063] The anti-fingerprint coating 5 is a water-soluble polyurethane layer with a thickness of 2μm.
[0064] Example 2
[0065] This embodiment provides a composite tape with a total thickness of 40μm, and the cross-sectional structure is shown in the figure below. Figure 1 As shown, it includes a release liner layer 1, an adhesive layer 2, a base film layer 3, a black ink layer 4, an anti-fingerprint coating 5, and a composite substrate layer 6 arranged sequentially.
[0066] Among them, the profile layer 1 is a PET layer with a thickness of 25μm;
[0067] Adhesive layer 2 is made of the acid-free pressure-sensitive adhesive from Preparation Example 1, and has a thickness of 10 μm.
[0068] The base film layer 3 is a polyimide layer with a thickness of 2 μm;
[0069] Black ink layer 4 is a carbon black ink layer with a thickness of 2μm;
[0070] The anti-fingerprint coating 5 is a water-soluble polyurethane layer with a thickness of 1μm.
[0071] Example 3
[0072] This embodiment provides a composite tape with a total thickness of 84μm, and the cross-sectional structure is shown in the figure below. Figure 1 As shown, it includes a release liner layer 1, an adhesive layer 2, a base film layer 3, a black ink layer 4, an anti-fingerprint coating 5, and a composite substrate layer 6 arranged sequentially.
[0073] Among them, the profile layer 1 is a PET layer with a thickness of 34μm;
[0074] Adhesive layer 2 is made of the acid-free pressure-sensitive adhesive from Preparation Example 1, and has a thickness of 22 μm.
[0075] The base film layer 3 is a polyimide layer with a thickness of 20 μm;
[0076] Black ink layer 4 is a carbon black ink layer with a thickness of 5μm;
[0077] The anti-fingerprint coating 5 is a water-soluble polyurethane layer with a thickness of 3μm.
[0078] Comparative Example 1
[0079] The only difference from Example 1 is that the base film layer and the black ink layer are replaced with a black substrate (Dongfang, D250) with a total thickness of 5μm. All other structures and parameters are the same as in Example 1.
[0080] Comparative Example 2
[0081] The only difference from Example 1 is that the acid-free acrylic adhesive layer is replaced with the acrylic adhesive layer of Preparation Example 2, while the other structures and parameters are the same as in Example 1.
[0082] Performance testing
[0083] (1) Peel strength: Tested according to the method provided in GB / T2792-2014.
[0084] (2) Holding power: The test shall be conducted in accordance with the method provided in GB / T4851-2014.
[0085] (3) Light transmittance: Tested according to the method provided in GB / T2410-2008.
[0086] (4) Acid value: Tested according to the method provided in GB / T2895-2008.
[0087] The composite tapes provided in the examples and comparative examples were tested according to the above test methods, and the test results are shown in Table 1:
[0088] Table 1
[0089]
[0090] As can be seen from the data in Table 1, the composite tape provided by this utility model has good adhesion, peel strength greater than 1000gf / inch, and can continuously suspend weights for more than 7 days without failure under high temperature and high humidity (80℃, 85%RH) conditions. It also has excellent light-blocking effect, light transmittance ≤0.05%, and acid value of 0mg KOH / g.
[0091] As can be seen from the comparison between Example 1 and Comparative Example 1, when using a single black substrate, the light transmittance increases from 0.01% to 0.80%, and the light-blocking effect decreases significantly. There is a risk of light leakage when using it in certain special areas inside electronic products.
[0092] As can be seen from the comparison between Example 1 and Comparative Example 2, the acid value of the acrylic composite tape provided by Comparative Example 2 is 35 mgKOH / g, which poses a risk of corroding the internal components of electronic products; at the same time, the peel strength is reduced, the high temperature and high humidity holding power drops after 1 day, and the high temperature and high humidity resistance is poor.
[0093] The applicant declares that this utility model illustrates a composite tape, a display module, and an OLED screen through the above embodiments, but this utility model is not limited to the above embodiments, that is, it does not mean that this utility model must rely on the above process steps to be implemented. Those skilled in the art should understand that any improvements to this utility model, equivalent substitutions of the raw materials used in this utility model, additions of auxiliary components, and selection of specific methods, etc., all fall within the protection and disclosure scope of this utility model.
Claims
1. A composite tape, characterized in that, The composite tape includes a composite substrate layer, an adhesive layer, and a release liner layer arranged sequentially. The composite substrate layer includes a base film layer, a black ink layer, and an anti-fingerprint coating; The adhesive layer includes an acid-free pressure-sensitive adhesive layer.
2. The composite tape according to claim 1, characterized in that, The base film layer includes a polyester film layer or a polyimide layer; The thickness of the base film layer is 2-20 μm.
3. The composite tape according to claim 1, characterized in that, The black ink layer includes a carbon black ink layer; The thickness of the black ink layer is 2-5 μm.
4. The composite tape according to claim 1, characterized in that, The anti-fingerprint coating includes a water-soluble polyurethane layer; The thickness of the anti-fingerprint coating is 1-3 μm.
5. The composite tape according to claim 1, characterized in that, The thickness of the composite substrate layer is 5-28 μm.
6. The composite tape according to claim 1, characterized in that, The thickness of the adhesive layer is 10-22 μm.
7. The composite tape according to claim 1, characterized in that, The release liner layer includes a polyester release liner; The thickness of the release liner is 25-50 μm.
8. The composite tape according to claim 1, characterized in that, The thickness of the composite tape is 40-100μm.
9. A display module, characterized in that, The display module includes the composite tape as described in any one of claims 1-8.
10. An OLED screen, characterized in that, The OLED screen includes the display module as described in claim 9.
Citation Information
Patent Citations
Shading adhesive tape
CN205188195U
Shading tape
CN213388482U